Lapatinib antitumor effect is associated with PI3K and MAPK pathway: An analysis in human and canine prostate cancer cells - Fonseca-Alves, Carlos Eduardo [UNESP]; Leis-Filho, Antonio Fernando [UNESP]; Lacerda, Zara Alves [UNESP]; de Faria Lainetti, Patricia [UNESP]; Amorim, Renee Laufer [UNESP]; Rogatto, Silvia Regina (Public Library of Science (PLoS), 2024)
The aberrant activation of HER2 has a pivotal role in bone metastasis implantation and progression in several tumor types, including prostate cancer (PC). Trastuzumab and other anti-HER2 therapies, such as lapatinib, have been used in human breast cancer HER2 positive. Although HER2 overexpression has been reported in PC, anti-HER2 therapy response has revealed conflicting results. We investigated the potential of lapatinib in inhibiting cell migration and inducing apoptosis in two human (LNCaP and PC3) and two canine PC cell lines (PC1 and PC2). Cell migration and apoptosis were evaluated by Annexin V/PI analysis after lapatinib treatment. The transcriptome analysis of all cell lines before and after treatment with lapatinib was also performed. We found increased apoptosis and migration inhibition in LNCaP cells (androgen-sensitive cell line), while PC1, PC2, and PC3 cells showed no alterations after the treatment. The transcriptome analysis of LNCaP and PC3 cell lines showed 158 dysregulated transcripts in common, while PC1 and PC2 cell lines presented 82. At the doses of lapatinib used, we observed transcriptional modifications in all cell lines. PI3K/AKT/mTOR pathway were enriched in human PC cells, while canine PC cells showed enrichment of tyrosine kinase antitumor response and HER2-related pathways. In canine PC cells, the apoptosis failed after lapatinib treatment, possibly due to the downregulation of MAPK genes. Prostate cancer cells insensitive to androgens may be resistant to lapatinib through PI3K gene dysregulation. The association of lapatinib with PI3K inhibitors may provide a more effective antitumor response and clinical benefits to PC patients.